The Effects of Photobiomodulation (Red Light Therapy) on Delayed Onset Muscle Soreness (DOMS) and Muscle Recovery in Adults: A Narrative Review - Wiercioch, Eliza; Wieleba, Marcin; Włodarczyk, Franciszek; Krupska, Barbara; Zapalska, Magdalena; Winiarska, Zuzanna; Woźniak, Weronika; Kulig, Lidia; Malec, Julia; Woszczek, Michał (Quality in Sport, 2026)
Background. Photobiomodulation (PBM) has gained attention as a potential non-invasive strategy to enhance muscle recovery following exercise-induced muscle damage. However, its effectiveness remains inconsistent across studies in human trials. Objective. The aim of this review was to critically evaluate the effects of PBM on delayed onset muscle soreness (DOMS), functional muscle recovery, and biochemical markers of muscle damage in humans. Methods. A narrative review of recent studies investigating PBM in the context of exercise-induced muscle damage was conducted. Relevant articles were identified through electronic databases and analysed qualitatively. Results. Most studies suggest that PBM may reduce DOMS, improve recovery of muscle function, and attenuate biochemical markers such as creatine kinase. Mechanistic evidence supports enhanced mitochondrial activity, increased ATP production, and modulation of oxidative stress and inflammation as potential pathways for these effects. However, some studies reported no significant benefits, reflecting variability in PBM parameters, timing of application, exercise modalities, and participant characteristics. Conclusion. PBM shows promise as a supportive recovery strategy for athletes and physically active individuals, particularly in contexts requiring rapid post-exercise recovery. Nevertheless, standardized treatment protocols and further high-quality studies are necessary to confirm its efficacy and determine optimal application parameters.